KONSEP KEPEMILIKAN DAN DISTRIBUSI DALAM EKONOMI ISLAM - Nuri Aslami; Sri Sudiarti (Politeknik Bisnis Indonesia, 2022)
Since the time of the Prophet, the issue of ownership has existed and resurfaced. However, the meaning of the phrase, also known as